A Volumetric Absorptive Microsampling Technique to Monitor Cannabidiol Levels in Epilepsy Patients - Dubois, Sara; Marchese, Francesca; Pigliasco, Federica; Barco, Sebastiano; Tripodi, Gino; Lomonaco, Tommaso; Lattanzi, Simona; Russo, Emilio; Cangemi, Giuliana; Striano, Pasquale (Frontiers in Pharmacology, 2020)
Purpose: Interest in cannabis-based therapies has recently increased, due to the availability of cannabidiol (CBD) for the treatment of epilepsy without psychoactive effects. Therapeutic drug monitoring can prevent drug interactions and minimize drug toxicity. We evaluated a volumetric absorptive microsampling (VAMS) method combined with LC-MS/MS (liquid chromatography coupled to tandem mass spectrometry) for the quantification of CBD blood levels in patients with refractory epilepsy. Methods: Prospective observation of patients with Dravet syndrome receiving open-label, add-on GW-purified CBD (Epidyolex®) at different doses. CBD plasma samples were obtained from venipuncture and LC-MS/MS was used to measure CBD in venous and capillary blood samples collected by VAMS. Results: We enrolled 5 patients with a mean age of 13 (range: 4-27) years. CBD levels measured by VAMS on capillary blood did not differ from CBD levels measured in plasma by venipuncture (R2>0.93). Conclusions: This proof-of-concept study suggests that VAMS allows monitoring of CBD plasma levels and can offer valuable support for personalized therapy in refractory epilepsy.